Association between serum 25-hydroxyvitamin D and glycated hemoglobin levels in type 2 diabetes patients with chronic kidney disease - Lim, Lee Ling; Ng, Yong Muh; Kang, Pei San; Lim, Soo Kun (Wiley Open Access, 2017)
Aims/Introduction: Vitamin D is suggested to influence glucose homeostasis. An inverse relationship between serum 25-hydroxyvitamin D (25[OH]D) and glycemic control in non-chronic kidney disease (CKD) patients with type 2 diabetes was reported. We aimed to examine this association among type 2 diabetes patients with CKD. Materials and Methods: A total of 100 type 2 diabetes participants with stage 3–4 CKD were recruited. Blood for glycated hemoglobin (HbA 1c ), serum 25(OH)D, renal and lipid profiles were drawn at enrollment. Correlation and regression analyses were carried out to assess the relationship of serum 25(OH)D, HbA 1c and other metabolic traits. Results: A total of 30, 42, and 28% of participants were in CKD stage 3a, 3b and 4, respectively. The proportions of participants based on ethnicity were 51% Malay, 24% Chinese and 25% Indian. The mean (±SD) age and body mass index were 60.5 ± 9.0 years and 28.3 ± 5.9 kg/m 2 , whereas mean HbA 1c and serum 25(OH)D were 7.9 ± 1.6% and 37.1 ± 22.2 nmol/L. HbA 1c was negatively correlated with serum 25(OH)D (r s = −0.314, P = 0.002), but positively correlated with body mass index (r s = 0.272, P = 0.006) and serum low-density lipoprotein cholesterol (P = 0.006). There was a significant negative correlation between serum 25(OH)D and total daily dose of insulin prescribed (r s = −0.257, P = 0.042). Regression analyses showed that every 10-nmol/L decline in serum 25(OH)D was associated with a 0.2% increase in HbA 1c . Conclusions: Lower serum 25(OH)D was associated with poorer glycemic control and higher insulin use among multi-ethnic Asians with type 2 diabetes and stage 3–4 CKD.